Multiple modernities: konkurrierende Thesen und offene Fragen: ein Literaturbericht in konstruktiver Absicht = Multiple modernities : competing theses and open questions - Schwinn, Thomas (Zeitschrift für Soziologie, 2009)
The multiple-modernities approach is developed in confrontation with alternative theories and by answering open questions. First, the basic problems of defining different types of modernity will be explained (1). In contrast to the idea of multiple patterns of modernity, neo-modernization theory claims there is a growing similarity between modernizing societies. This is based on the model of the fixed interdependencies of modern institutions (2). Furthermore, it is supposed that culture follows structure. That is why the effects of culture on patterns of modernity must be scrutinized in detail (3). World-systems approaches deny the existence of multiple modernities (4). Comparative research on forms of capitalism identifies a so-called Rhine-type of capitalism which cuts across civilizational units. The question arises as to whether variation develops as independent of or as dependent on cultural sources (5). These theoretical insights are used to clarify tacit assumptions within the debate on the entry of Turkey into the EU (6). Finally, open questions requiring further research are enumerated (7).